The Cost of Annuities: Implications for Saving Behavior and Bequests - Friedman, Benjamin M.; Warshawsky, Mark J. (Quarterly Journal of Economics, 1990)
The fact that most eldealy individuals in the United States choose to maintain a flat age-wealth profile, rather than buy individual life annuities, stands in contrast to central implications of the standard life-cycle model of consumption-saving behavior. The analysis in this paper lends support to an explanation for this phenomenon based either on the cost of annuities, importantly including the element of that cost due to adverse selection, or on the interaction of that cost and an intentional bequest motive. Expected yields offered on individual life annuities in the United States are lower by some 4-6%, or 2 1/2-4 1/2% after allowing for adverse selection, than yields on alternative long-term fixed-income investments. Simulations of an extended model of life-cycle saving and portfolio behavior, allowing explicitly for uncertain lifetimes and Social Security, show that yield differentials in this range can account for the observed behavior, even in the absence of a bequest motive, during the early years of retirement. By contrast, at older ages the combination of yield differentials in this range and a positive bequest motive is necessary to do so.